2016
DOI: 10.1158/0008-5472.can-15-1796
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PAI-1 Limits Tumor Angiogenesis Regardless of Angiogenic Stimuli in Malignant Pleural Mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is an aggressive malignant tumor that secretes various angiogenic factors. The main inhibitor of plasminogen activators, PAI-1 (SERPINE1), has been implicated in tumor progression and angiogenesis, and high PAI-1 expression has been associated with poor prognosis in MPM patients. In this study, we examined the antiangiogenic effects of PAI-1 inhibition in MPM. We administered the PAI-1 inhibitor, SK-216, to orthotopic mouse models in which MPM cells expressing high levels o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 38 publications
(38 reference statements)
2
33
0
1
Order By: Relevance
“…Conversely, miRNA-145 was shown to inhibit GC cell invasion, metastasis and angiogenesis by targeting v-ets erythroblastosis virus E26 oncogene homolog 1 (39). Additionally, inhibition of miRNA-mediated SERPINE1 limits tumor angiogenesis, regardless of the angiogenic stimuli, in malignant pleural mesothelioma (40). In the present study, it is found that SERPINE1 is a direct target of miR-145-5p.…”
Section: Discussionsupporting
confidence: 45%
“…Conversely, miRNA-145 was shown to inhibit GC cell invasion, metastasis and angiogenesis by targeting v-ets erythroblastosis virus E26 oncogene homolog 1 (39). Additionally, inhibition of miRNA-mediated SERPINE1 limits tumor angiogenesis, regardless of the angiogenic stimuli, in malignant pleural mesothelioma (40). In the present study, it is found that SERPINE1 is a direct target of miR-145-5p.…”
Section: Discussionsupporting
confidence: 45%
“…PAI‐1 has been also reported to be involved in resistance to chemotherapy and tumourigenesis in various types of cancers . In vivo studies revealed the significance of PAI‐1 in regulating tumour angiogenesis . Furthermore, several in vitro studies have shown that PAI‐1 has a direct pro‐proliferative and anti‐apoptotic effect on the cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Sca-1 + cell secretome is composed of a variety of cytoprotective molecules that were comparably secreted in both conditions such as inhibitors of apoptosis like IGF1 and SRPF2 (Vinciguerra, Santini, Claycomb, Ladurner, & Rosenthal, 2009;Zhang et al, 2009), WISP2 known to induce proliferation (Chowdhury et al, 2014) and the proangiogenic VEGFD (Jauhiainen et al, 2011) Angiogenesis is a dynamic process, which is tightly regulated by pro-and anti-angiogenic factors. Our data show a higher secretion of several angiogenic promoters namely MFGM, MYDGF, ANGP2, and PAI1 (Leblond et al, 2015;Mazzieri et al, 2011;Takayama et al, 2016;Uchiyama et al, 2014), as well as of inhibitors such as PEDF and TSP2 (Cai, Jiang, Grant, & Boulton, 2006;Krady et al, 2008) in Cyc cells than in Wt cells. Beside we observed no remarkable difference in the relative abundance of positive versus negative regulators in either CM.…”
Section: Recentmentioning
confidence: 54%